Understanding urban ecologies in the context of local biodiversity and open space conservation agendas in two South African cities - Bux, Quraisha (Department of Environmental and Geographical Science, 2019)
South Africa is the third most biologically diverse country in the world and has developed advanced biodiversity legislation and policies to protect its natural environment. Biodiversity is the natural wealth of all living things on earth, from which a multitude of ecosystem services that sustain life emanate. The dramatic shift towards urban living however, places tremendous pressure on these biological resources. Local government has received international recognition as the level of government that is key to securing long-term global sustainability. The cities of Cape Town and Durban in South Africa have each developed their own biodiversity and open space conservation systems to conserve and protect the remaining biodiversity and open spaces within their respective municipal boundaries. The aim of this research was to explore the local biodiversity and open space conservation strategies in these two cities, with a view to understanding: (1) the informants, and emerging form, of urban conservation strategies in these two cities in light of their variable biophysical templates and histories; and (2) the physical landscape pattern in each city, and from this information, infer likely ecological outcomes, for these two cities. The study made use of both qualitative and quantitative research methods. The results reveal that while both cities are facing similar issues in terms of biodiversity loss and natural habitats becoming increasingly fragmented, the way in which these issues manifest in these different cities is unique. The City of Cape Town is highly developed and fragmented but has more land secured under its conservation plan compared to the City of Durban. Durban however, has a large rural land component which remains under the governance of traditional leaders. The study reveals that there are many factors that play a role in the development and success of conservation plans, including: the local context, biophysical templates, city histories, social informants of how these plans emerge and evolve, contemporary governance structures as well as local pressures. Biodiversity conservation in South African cities still faces many challenges which need to be overcome in the near future. These solutions will need to be city specific.